2008
DOI: 10.1073/pnas.0810133105
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent domains enforce transcriptional memory of DNA methylated genes in cancer cells

Abstract: Silencing of multiple cancer-related genes is associated with de novo methylation of linked CpG islands. Additionally, bivalent histone modification profiles characterized by the juxtaposition of active and inactive histone marks have been observed in genes that become hypermethylated in cancer. It is unknown how these ambiguous epigenetic states are maintained and how they interrelate with adjacent genomic regions with different epigenetic landscapes. Here, we present the analysis of a set of neighboring gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
84
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 33 publications
14
84
0
Order By: Relevance
“…These genes are silenced in a promoter methylationindependent manner. However, there is evidence that methylation does play a part, as the PcG protein EZH2 directly controls promoter hypermethylation at target genes and PcGs fold hypermethylated DNA into loops, which appear to enforce epigenetic silencing [87][88][89]. PcG proteins thus mediate their repressive effect by inducing classical epigenetic modifications and architectural changes of the chromatin.…”
Section: Polycomb Group Proteinsmentioning
confidence: 99%
“…These genes are silenced in a promoter methylationindependent manner. However, there is evidence that methylation does play a part, as the PcG protein EZH2 directly controls promoter hypermethylation at target genes and PcGs fold hypermethylated DNA into loops, which appear to enforce epigenetic silencing [87][88][89]. PcG proteins thus mediate their repressive effect by inducing classical epigenetic modifications and architectural changes of the chromatin.…”
Section: Polycomb Group Proteinsmentioning
confidence: 99%
“…It is interesting that, hypermethylation of these CpG islands was accompanied by long-range epigenetic silencing (LRES) of a 4-Mb chromosomal region mapping at 2q14.2 affecting all the genes regardless of whether their promoters were associated with CpG islands and if these were methylated or not (Frigola et al, 2006). Beyond this first evidence supporting, the existence of a new mechanism of gene inactivation in cancer, later studies indicate that LRES may also occur in other chromosomal regions and cancers (Stransky et al, 2006;Hesson et al, 2007;Hitchins et al, 2007;Rodriguez et al, 2008). This region encompasses the Engrailed-1 (EN1) gene encoding a homeobox transcription factor.…”
mentioning
confidence: 99%
“…First group consists of silenced genes exhibiting methylated CpG island-promoter; this group includes EN1, SCTR and INHBB (2q14.2) and HRH2, CPLX2 and SNCB (5q35.2) that express at low levels in normal colon cells. 3,6 A second group consisted of genes with unmethylated CpG island-promoter, and includes DDX18, INSIG2, PTPN4, RALB, TSN (2q14.2), SFXN1 and THOC3 (5q35.2). These genes tend to be downregulated in colorectal tumors (as compared with the normal colon cells) but still retain high expression levels.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…12,13 Different studies have reported that in genes that become silenced in cancer cells, the repressive mark H3K27me3 co-exists with active marks (H3K4me3 and H3K4me2). 6,14,15 These two opposite modifications participate in the mitotic inheritance of lineagespecific gene expression programs and have key developmental functions. Its co-localization is considered characteristic of stem cells and is believed to keep developmental regulator genes poised for induction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation